Influence of in‐amphorae vinification on the molecular profile of Sangiovese and Cabernet Franc. (7th May 2022) - Martellini, Tania; Sposato, Laura; Pucci, Susanna; Meoni, Gaia; Marinelli, Cristian; Tenori, Leonardo; Luchinat, Claudio; Giorgi, Rodorico; Sarti, Chiara; Cincinelli, Alessandra
Abstract: In the last decade, some wine producers have re‐evaluated the role of micro‐oxygenation guaranteed by the porosity of the earthenware in the fermentation and refinement phases and, thus, the potential and limitations of this technique on the flavour and aromatic profile of wine need further investigations. The wine volatile profile was analysed by headspace solid phase microextraction coupled with gas chromatography—mass spectrometry, and the volatile compound percentages in Sangiovese and Cabernet Franc vinified in Stainless Steel Containers and in amphorae over time were compared. Results showed that the in‐amphorae vinification enhances the aromatic components of the Cabernet Franc wine, while there is no substantial difference for Sangiovese wine. A metabolomic approach was also attempted for the first time, and the NMR analysis highlighted a difference between the spectra of the samples vinified in‐amphorae with respect to those vinified in steel suggesting a potential new approach to obtain a significant traceability. Abstract : The influence of in‐amphorae winemaking on the volatile profile of two different type of wines was evaluated. The volatile profile highlighted a different effect based on the type of grape used; a metabolomic approach was applied for the traceability of wines in amphora.